Effectiveness of Inner Traction-Facilitated Endoscopic Submucosal Dissection Using Rubber Band and Clips for Colorectal Neoplasms: A Propensity Score-Matched Study - Guanyi Liu,; Xinyue Guo,; Yunlong Cai,; Long Rong,; Weidong Nian,; Jixin Zhang, (Turkish Journal of Gastroenterology, 2023)
Background: Colorectal endoscopic submucosal dissection is a technically demanding but effective treatment for superficial neoplasms. We conducted a study to compare the effectiveness and safety of inner traction-facilitated endoscopic submucosal dissection using rubber band and clip with conventional endoscopic submucosal dissection.Methods: We retrospectively evaluated 622 consecutive patients who underwent colorectal endoscopic submucosal dissection between January 2016 and December 2019. To overcome selection bias, we used propensity score matching (1:4) between endoscopic submucosal dissection using rubber band and clip and conventional endoscopic submucosal dissection. The frequency of en bloc resections, R0 resections, curative resections, procedure speed, and complications were evaluated.Results: After propensity score matching, 35 patients were included in the endoscopic submucosal dissection using rubber band and clip group and 140 were included in the conventional endoscopic submucosal dissection group. Endoscopic submucosal dissection using rubber band and clip resulted in a significant increase in resection speed (0.14 vs. 0.09 cm2/min; P = .003). There were no significant differences in en bloc, R0, and curative resection rates between the 2 groups. In subgroup analysis, the resection speed of endoscopic submucosal dissection using rubber band and clip was significantly higher than that of conventional endoscopic submucosal dissection when the lesions were equal to or larger than 2 cm, macroscopically presenting as lateral spreading tumor, and located in transverse colon to ascending colon.Conclusions: Endoscopic submucosal dissection using rubber band and clip is safe and effective in treating colorectal neoplasms, especially in lesions presenting a particular difficulty.Cite this article as: Liu G, Guo X, Cai Y, Rong L, Nian W, Zhang J. Effectiveness of inner traction-facilitated endoscopic submucosal dissection using rubber band and clips for colorectal neoplasms: A propensity score-matched study. Turk J Gastroenterol. 2023;34(4):364-370